Altered mitochondrial unfolded protein response and FGF21 secretion in MASLD progression and the effect of exercise intervention - Xinmeng Yuan; Wen Sun; Ye Xu; Mengqi Xiang; Yaran Gao; Wanyu Feng; Hongjian Xiao; Liumei Zhang; Qiang Tang; Jiao Lu; Yuan Zhang (Scientific Reports)
Abstract A high-calorie diet and lack of exercise are the most important risk factors contributing to metabolic dysfunction-associated steatotic liver disease (MASLD) initiation and progression. The precise molecular mechanisms of mitochondrial function alteration during MASLD development remain to be fully elucidated. In this study, a total of 60 male C57BL/6J mice were maintained on a normal or amylin liver NASH (AMLN) diet for 6 or 10 weeks. Some of the mice were then subjected to voluntary wheel running, while the other mice were fed a normal or AMLN diet until 14 and 18 weeks. The results showed that hepatic lipid deposition and the PERK-eIF2α-ATF4 pathway were significantly increased with prolonged duration of AMLN diet. However, expression of mitochondrial unfolded protein response (UPRmt) genes and mitokine FGF21 secretion were significantly enhanced in the 14-week AMLN diet mice, but were markedly reduced with the excessive lipid deposition induced by longer AMLN diet. Additionally, the exercise intervention acts as a regulator to optimize UPRmt signal transduction and to enhance mitochondrial homeostasis by improving mitochondrial function, reversing the UPRmt activation pattern, and increasing FGF21 secretion, which plays a pivotal role in delaying the occurrence and development of MASLD.